2023
DOI: 10.3390/microorganisms11071749
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Gestational Diabetes and the Microbiome: A Systematic Review and Meta-Analysis

Abstract: Gestational diabetes, affecting about 10% of pregnancies, is characterized by impaired glucose regulation and can lead to complications for health of pregnant women and their offspring. The microbiota, the resident microbes within the body, have been linked to the development of several metabolic conditions. This systematic review with meta-analysis aims to summarize the evidence on the differences in microbiota composition in pregnant women with gestational diabetes and their offspring compared to healthy pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Next, using the FITC-dextran method, it was shown that, as expected, in non-pregnant mice on a HFD, there was a 2-fold increase in gut permeability, whereas in pregnant mice fed chow, there was a 1.5-fold increase in gut permeability, and these findings mostly reproduce those of previous studies [12,16,[20][21][22]. Conversely, pregnancy completely abolished the harmful effect of the HFD on gut barrier integrity, and, to our knowledge, this has never been described before.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Next, using the FITC-dextran method, it was shown that, as expected, in non-pregnant mice on a HFD, there was a 2-fold increase in gut permeability, whereas in pregnant mice fed chow, there was a 1.5-fold increase in gut permeability, and these findings mostly reproduce those of previous studies [12,16,[20][21][22]. Conversely, pregnancy completely abolished the harmful effect of the HFD on gut barrier integrity, and, to our knowledge, this has never been described before.…”
Section: Discussionsupporting
confidence: 85%
“…Prior studies have described in detail the effects of a HFD on gut barrier integrity and also on the gut microbiome landscape [16,20,21]. In addition, there are some studies that have evaluated the same parameters in pregnancy [12,22]. However, little was known about the impact of pregnancy on gut permeability and microbiota in diet-induced obesity [2,13,19].…”
Section: Discussionmentioning
confidence: 99%
“…Both type 1 and type 2 diabetes in mothers are associated with an increased risk of CHD in the offspring [ 37 ]. Changes in the composition of the gut microbiota, such as an increase in Firmicutes and a decrease in Bacteroidetes and Actinobacteria, have been observed in pregnancies with GDM [ 38 ], and the recent literature only highlights how much potential there is for microbiome-targeted therapies in gestational diabetes [ 39 ].…”
Section: Microbiome and Metabolomics In The Context Of Chd And Beyondmentioning
confidence: 99%